Edgar Kant, Estonian geography and the reception of Walter Christaller's central place theory, 1933–1960. (April 2018) - Tammiksaar, Erki; Jauhiainen, Jussi S.; Pae, Taavi; Ahas, Rein
Abstract: As a result of the First World War several new nation-states emerged on the map of Europe. One of them was the Republic of Estonia, emerging from the ruins of the Russian Empire. As Estonians had never had their own state before, the establishment of the parliamentary republic, its institutions and a national identity was a big challenge for its small elite. First and foremost, the ambition was to do things differently from the previous rulers. The Estonian economic geographer Edgar Kant played an important role in the development of his country between 1920 and 1940. His geography was politically motivated, innovative and pragmatic as the rapid development of the state required new theories and methods. The methodological basis for Kant's 'innovative geography' became Walter Christaller's central place theory, and he was the first in the world to understand the importance of applying it in empirical research, doing so in the 1930s in the reform of Estonian rural municipalities. In September 1944, Edgar Kant fled from Estonia to Lund and Christaller's theory spread more widely through Kant's interactions with Torsten Hägerstrand in Sweden and later Edward Ullman and Brian Berry in the United States. This paper reviews the relatively unknown geography, and the complicated life, of Edgar Kant, who, it is argued, strongly influenced the trajectory of the triumph of the 'new geography' in the 1950s. Through this example it will be shown how peripheral actors and places can play key roles in innovation diffusion and intellectual history. Highlights: Analyzes the reception of Walther Christaller's central place theory from the 1930s to the 1950s. Shows the significance of an Estonian geographer Edgar Kant in promoting the quantitative revolution in geography. Argues that Edgar Kant was the first in the world to understand the practical value of central place theory. Shows the importance of a scientist from peripheral place to the course of intellectual history.